Հիզտբուզիտի վկայաբանության պատմականությունը - Ազատյան, Շավարշ (ՀՀ ԳԱԱ հրատ.)
Мартирология Изтбузита – одно из важнейших литературных произведений армянской агиографии, содержащее исторические данные о марзпанской Армении и Сасанидском Иране․ Martyrology of Hiztbuzit is an important literary work of Armenian Hagiography that has multidisciplinary historical knowledge about Armenia of the Marzpanate period and the Sasanian Empire.
Keywords: Հայագիտություն; Պատմություն